2020
DOI: 10.2196/19416
|View full text |Cite
|
Sign up to set email alerts
|

A Human-Algorithm Integration System for Hip Fracture Detection on Plain Radiography: System Development and Validation Study

Abstract: Background Hip fracture is the most common type of fracture in elderly individuals. Numerous deep learning (DL) algorithms for plain pelvic radiographs (PXRs) have been applied to improve the accuracy of hip fracture diagnosis. However, their efficacy is still undetermined. Objective The objective of this study is to develop and validate a human-algorithm integration (HAI) system to improve the accuracy of hip fracture diagnosis in a real clinical envir… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 41 publications
0
11
0
Order By: Relevance
“…( 80,83,85,91 ) In addition, a recent study further validated one of the reviewed studies ( 78 ) and demonstrated how AI recommendations were able to improve the identification of hip fractures in clinical routine. ( 132 ) Prediction and diagnosis models increasingly prove to be more accurate than experts, expanding on the limits of human performance. This raises the ethical question whether AI decisions may have undesired side effects.…”
Section: Discussionmentioning
confidence: 99%
“…( 80,83,85,91 ) In addition, a recent study further validated one of the reviewed studies ( 78 ) and demonstrated how AI recommendations were able to improve the identification of hip fractures in clinical routine. ( 132 ) Prediction and diagnosis models increasingly prove to be more accurate than experts, expanding on the limits of human performance. This raises the ethical question whether AI decisions may have undesired side effects.…”
Section: Discussionmentioning
confidence: 99%
“…Among the included studies, the architecture based on the GoogLeNet architectural model [ 7 , 11 , 18 ] or the DenseNet architectural model [ 13 , 14 , 20 ] was the most common with three each. Among the data input proportions, the study of Adams et al had the lowest training rate of 57% [ 11 ], and the study of Yamada et al had the largest training rate of 95% [ 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…In 14 studies, 5 studies used Grad-CAM for highlight important regions. The information on AI for all included studies is presented in Table 3 [ 1 , 8 , 16 , 20 , 21 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…There have been some papers on the use of a deep learning algorithm to diagnose hip fractures. Some of these studies diagnose from antero-posterior images only [ 17 20 ], one from both antero-posterior and lateral images [ 21 ], one can predict not only presence of fractures but also fracture type [ 22 ], and one of the same algorithms can be used to diagnose both proximal femur and pelvic fractures [ 23 ] . Additionally, a previous study reported that deep learning algorithm improved the diagnostic accuracy of fracture detection by clinicians [ 20 , 22 , 24 ].…”
Section: Introductionmentioning
confidence: 99%